Isolation of Zn and Cr in Biosolid Waste by Extraction Process Using Sulfuric Acid (Nusantara Science and Technology Proceedings)
This study investigates the separation of zinc and heavy chromium metals in biosolid waste by an extraction process using H2SO4 solvent. The extraction of the heavy chromium process was performed in biosolid waste of 100 mesh with various times and pH. The solid extracts were analyzed using the Atomic absorption spectrometry (AAS) analysis method. The most effective condition to decrease Zn and Cr levels were obtained at the extraction process 120 minutes, and the solvent concentration was 1.5 M with the efficiency of 98.80 % and 97.89 %, respectively.